Factors influencing the growth, production and reproduction of different breeds of beef cattle under range conditions in Southern Rhodesia - Vorster, T. H (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1962.